Implementasi Konsep Arsitektur High-Tech Pada Desain Fitness and Wellness Center di Pekanbaru - Rabudin Rizki; Gun Faisal; Yohannes Firzal (ARSITEKTURA, 2020)
Pekanbaru is a developing capital city that can be seen from the density of community activities in their daily lives. This requires having a fit and healthy body. A fit and healthy lifestyle is also an important requirement for the body. Fitness and good body beauty is the dream of every human being. Lack of fitness in the body will make you weak and less enthusiastic in carrying out your daily routine. From this problem, we need a place that accommodates fitness activities and physical and spiritual health of the body. Generally, Fitness and Wellness facilities in Pekanbaru are still located in shophouses, residences, shopping centers and part of the supporting facilities for star-rated hotels. Therefore a Fitness and Wellness Center is needed that expresses fitness and health by supporting various physical and physical and spiritual activities that have never existed before by presenting aesthetics, technology and building a supporting structure. For that, we need a high-tech architectural principles approach that exposes a structure that is not only load-bearing but also aesthetically pleasing to this building.